Preparation of Zn0.6Cd0.4o nanorods and its characterization - Mohamad, Souad A.; Othman, Raihan; Mushtaq, Umer (2013)
Hexagonal nanorods of Zn0.6Cd0.4O thin films were synthesized by electrodeposition technique using 0.6% of ZnCl2 and 0.4% of CdCl2 electrolytes. The synthesized Zn0.6Cd0.4O nanorods have uniform hexagonal crystallographic planes, and their diameters are about 100 nm. The ultra-violet (UV) near-band-edge (NBE) emission was red-shifted from 2.75 eV to 3.02 eV due to the direct tailoring of band gap caused by Cd/Zn substitution. The FESEM images of Zn0.6Cd0.4O confirms that hexagonal nanorods were first time synthesized via electrodeposition technique at temperature of 90 oC and the size of each regular face of hexagonal nanorods is about 63.6 nm. The characterizations for Zn0.6Cd0.4O were analyzed and the temperature is a key parameter for the formation of different morphologies of Zn0.6Cd0.4O nanostructures.